Mid-infrared laser techniques for sensing and imaging application - Fang, Bryan Zhongquan (2015)
This final year project is on gaining hands on experience on optics and photonics, as well as to develop a system to achieve better efficiency in producing results of quantum cascade lasers prototypes. Through observation in the lab, research students always have to waste time to position the laser diode to get its peak intensity collected from FTIR spectroscopy, with this problem I have decided to build a system to increase efficiency but before proceeding with building a system we first have to understand basic knowledge on quantum cascade lasers, mid-infrared detectors and direct absorption spectroscopy. This report shows the basic needs and understanding of quantum cascade lasers, how it works and functions followed by what is needed to detect QCLs and lastly, knowledge on direct absorption spectroscopy, with those information we can then proceed to the main part which will be the creation of the three-axis system to perform automatic detection of peak intensity to reduce human errors and increase efficiency.